2020
DOI: 10.14336/ad.2020.0205
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Roles Played by Immunosenescence in the Pathobiology of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a chronic progressive neurodegenerative disorder. Aging is the most significant risk factor for late-onset AD. The age-associated changes in the immune system are termed immunosenescence. A close connection between immunosenescence and AD is increasingly recognized. This article provides an overview of immunosenescence and evidence for its role in the pathogenesis of AD and possible mechanisms as well as the outlook for drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 142 publications
(175 reference statements)
0
14
0
Order By: Relevance
“…Immunosenescence is widely used to explain the catastrophic changes that can arise in dementia and the general inability of the elderly to resist immune challenge [ 66 ]. Recent work has indicated that the loss of pineal melatonin may underpin immunosenescence via the lost/suppressed night-time resetting of immune cell metabolism [ 29 ].…”
Section: Circadian Rhythm and Covid-19mentioning
confidence: 99%
“…Immunosenescence is widely used to explain the catastrophic changes that can arise in dementia and the general inability of the elderly to resist immune challenge [ 66 ]. Recent work has indicated that the loss of pineal melatonin may underpin immunosenescence via the lost/suppressed night-time resetting of immune cell metabolism [ 29 ].…”
Section: Circadian Rhythm and Covid-19mentioning
confidence: 99%
“…Thus, the innate cells are probably a cornerstone in driving the fate of immune responsiveness in old age resulting in inflammaging 27 and as such contributing to the development of AD. 65 , 66 …”
Section: Immunosenescence and Inflammaging: A Nutshell Descriptionmentioning
confidence: 99%
“…67,68 In the meantime, the anti-inflammatory mediators such as IL-10, IL-4, IL-13 may also be increased as a tentative measure to control this state. [61][62][63][64][65][66][67][68][69] Latent virus infections such as cytomegalovirus (CMV) infection, as well as commensal bacteria (eg bacteria in gut microbiome dysbiosis), may be reactivated and become harmful and contribute to inflammaging. [70][71][72][73] Indubitably, the finding that noninfectious agents can strongly contribute to the spreading of inflammatory processes has paved the way to extend the list of mechanisms that fuel inflammaging over time.…”
Section: Inflammagingmentioning
confidence: 99%
“…Redox imbalance in cells, as well as excessive or unregulated production of inflammatory mediators, is an element of the induction of neurodegenerative diseases, such as atherosclerosis, diabetes, Alzheimer’s disease, Parkinson’s disease and Huntington’s disease [ 28 , 29 , 62 ]. In neurodegenerative diseases, activated microglia is observed, which releases proinflammatory and anti-inflammatory cytokines and neurotoxic mediators.…”
Section: Bioactivity Of Polysaccharides From Ganoderma Lucidummentioning
confidence: 99%